1995
DOI: 10.1093/nar/23.3.320
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the yeast splicing factor PRP8 with substrate RNA during both steps of splicing

Abstract: PRP8 protein of Saccharomyces cerevisiae interacts directly with pre-mRNA in spliceosomes, shown previously by UV-crosslinking. To analyse at which steps of splicing and with which precursor-derived RNA species the interaction(s) take place, UV-crosslinking was combined with PRP8-specific immunoprecipitation and the coprecipitated RNA species were analysed. Specific precipitation of intron-exon 2 and excised intron species was observed. PRP8 protein could be UV-crosslinked to pre-mRNA in PRP2-depleted spliceos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…Recognition of the 59SS by base pairing to the 59 end of U1 snRNA represents one of the initial steps of spliceosome assembly+ While this interaction controls the overall selection of the 59 splice site, it does not specify the actual cleavage site (reviewed in Moore et al+, 1993;Nilsen, 1994)+ Subsequently, the 59SS:U1 snRNA basepairing must be disrupted to allow the 59SS to interact with Prp8, among other components of the U4/U5/U6 snRNP (see Kandels-Lewis & Séraphin, 1993;Konforti et al+, 1993;Lesser & Guthrie, 1993;Sontheimer & Steitz, 1993)+ Both human and yeast Prp8 have been shown to crosslink to the 59SS region (Wyatt et al+, 1992;Teigelkamp et al+, 1995aTeigelkamp et al+, , 1995bChiara et al+, 1996;Reyes et al+, 1996)+ We have previously shown that a highly specific GU dinucleotide:hPrp8 crosslink at the 59SS can be detected within splicing complex B assembled in trans-splicing reactions, where the 59SS is provided as a short RNA oligonucleotide (Reyes et al+, 1996)+ The analogous 59SS:hPrp8 crosslink can also be detected within complex B formed in cis-splicing reactions, using a unimolecular pre-mRNA substrate (Fig+ 1)+ Also the kinetics of crosslinking indicate that in both trans-and cis-splicing, the 59SS:hPrp8 interaction takes place early in the reaction, after formation of complex B, but before the appearance of splicing intermediates and products+ The interaction of Prp8 with exon sequences at the 59SS is maintained beyond the first step of splicing, as evidenced by the persistence of crosslinks in both yeast and mammalian systems (Wyatt et al+, 1992;Teigelkamp et al+, 1995b)+ In contrast, the GU:hPrp8 interaction described here occurs within spliceosome complex B, but crosslink formation is not detected at later stages in the reaction (Fig+ 1)+ This crosslinking profile suggests that either the GU:hPrp8 interaction is disrupted at later stages of splicing, or that an alteration in the physical environment near the contact site may not permit UV crosslinking, even though the interaction itself may be maintained+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of the 59SS by base pairing to the 59 end of U1 snRNA represents one of the initial steps of spliceosome assembly+ While this interaction controls the overall selection of the 59 splice site, it does not specify the actual cleavage site (reviewed in Moore et al+, 1993;Nilsen, 1994)+ Subsequently, the 59SS:U1 snRNA basepairing must be disrupted to allow the 59SS to interact with Prp8, among other components of the U4/U5/U6 snRNP (see Kandels-Lewis & Séraphin, 1993;Konforti et al+, 1993;Lesser & Guthrie, 1993;Sontheimer & Steitz, 1993)+ Both human and yeast Prp8 have been shown to crosslink to the 59SS region (Wyatt et al+, 1992;Teigelkamp et al+, 1995aTeigelkamp et al+, , 1995bChiara et al+, 1996;Reyes et al+, 1996)+ We have previously shown that a highly specific GU dinucleotide:hPrp8 crosslink at the 59SS can be detected within splicing complex B assembled in trans-splicing reactions, where the 59SS is provided as a short RNA oligonucleotide (Reyes et al+, 1996)+ The analogous 59SS:hPrp8 crosslink can also be detected within complex B formed in cis-splicing reactions, using a unimolecular pre-mRNA substrate (Fig+ 1)+ Also the kinetics of crosslinking indicate that in both trans-and cis-splicing, the 59SS:hPrp8 interaction takes place early in the reaction, after formation of complex B, but before the appearance of splicing intermediates and products+ The interaction of Prp8 with exon sequences at the 59SS is maintained beyond the first step of splicing, as evidenced by the persistence of crosslinks in both yeast and mammalian systems (Wyatt et al+, 1992;Teigelkamp et al+, 1995b)+ In contrast, the GU:hPrp8 interaction described here occurs within spliceosome complex B, but crosslink formation is not detected at later stages in the reaction (Fig+ 1)+ This crosslinking profile suggests that either the GU:hPrp8 interaction is disrupted at later stages of splicing, or that an alteration in the physical environment near the contact site may not permit UV crosslinking, even though the interaction itself may be maintained+…”
Section: Discussionmentioning
confidence: 99%
“…The mapped 59SS:hPrp8 crosslink does not represent the sole interaction between the pre-mRNA and Prp8+ Human Prp8 has been shown to crosslink to the branch site region within splicing complexes B and C (MacMillan et al+, 1994) and to sequences around the 39SS within splicing complex C, most likely after the first and before the second catalytic step (Chiara et al+, 1997)+ Similarly, yeast Prp8 forms crosslinks with the branch site region and the 39 exon after the first catalytic step (Teigelkamp et al+, 1995b)+ The involvement of Prp8 in the 39SS recognition is supported by the identification of the yeast PRP8 allele ( prp8-101) isolated as a suppressor of mutations in the polypyrimidine tract that selectively block the second step of splicing (Umen & Guthrie, 1995)+ A screen for additional mutations has defined two regions in the yPrp8 protein involved in fidelity of the 39SS choice and polypyrimidine tract recognition (Umen & Guthrie, 1996)+ A comparison of human and yeast Prp8 amino acid sequences indicates that the polypyrimidine tract recognition domain is located in close proximity to the 59SS RNA:hPrp8 crosslink+ The prp8-101 and prp8-102 alleles implicated in polypyrimidine tract recognition represent mutations of E (position 1960) in yPrp8, while the 59SS crosslink corresponds to positions 1966-1970 of the yeast protein+ This feature, together with the biochemical and genetic data indicating similar roles for yeast and human Prp8, suggests that the homologous region in yPrp8 is involved in recognition of the 59SS+…”
Section: Prp8 Interacts With Multiple Spliceosomal Componentsmentioning
confidence: 99%
“…An aliquot (10%) of each sample was analyzed for splicing activity ("splicing"), while the remainder was incubated with IgGagarose ("I") or, as controls, agarose beads ("B") or antiPrp8p antibodies ("C"). Prp8p is a U5 snRNP protein that is associated with the spliceosomes throughout the splicing reactions and should therefore precipitate the pre-mRNA, intermediates, and products of the splicing reaction as shown previously by Teigelkamp et al (1995b). To assess background precipitation by the protein A epitope, extract was prepared from strain BMA38a (pNOPPATAIL) in which the protein A epitope alone ("protA") was produced.…”
Section: Spliceosomal Association Of Prp45pmentioning
confidence: 99%
“…Snu114 regulates Brr2 activity in a nucleotide-dependent manner, repressing Brr2 activity in its GDP-bound form and activating in its GTP-bound form (Small et al 2006;Bellare et al 2008). Prp8, which accommodates the catalytic snRNAs and pre-mRNA substrate in a central cavity (Newman et al 1995;Teigelkamp et al 1995;Galej et al 2013;Yan et al 2015), has been shown to regulate Brr2 activity through its RNaseH (Mozaffari-Jovin et al 2012) and Jab1/MPN domains (Maeder et al 2009;Mozaffari-Jovin et al 2013). These proteins show multiple strong genetic (Kuhn et al 2002;Bottner et al 2005;Grainger and Beggs 2005;Liu et al 2006), yeast-two-hybrid (van Nues andBeggs 2001), and physical interactions , indicating a high degree of coordination between them.…”
Section: Introductionmentioning
confidence: 99%